Design, synthesis and biological evaluation of N-arylsulfonyl carbazoles as novel anticancer agents. Issue 31 (10th May 2018) - You, Xin; Zhu, Daqian; Lu, Wenhua; Sun, Yichen; Qiao, Shuang; Luo, Bingling; Du, Yongliang; Pi, Rongbiao; Hu, Yumin; Huang, Peng; Wen, Shijun
Abstract : In this work, a set of structurally diverse synthetic carbazoles was screened for their anticancer activities. Abstract : In this work, a set of structurally diverse synthetic carbazoles was screened for their anticancer activities. According to structure–activity relationship studies, carbazoles with an N -substituted sulfonyl group exhibited better anticancer activity. Moreover, compound8h was discovered to show the most potent anticancer effects on Capan-2 cells by inducing apoptosis and cell cycle arrest in G2/M phase. Finally, the in vivo study demonstrated that8h prevented the tumor growth in PANC-1 and Capan-2 xenograft models without apparent toxicity.